Purwarupa Web Dolan Muria Dalam Upaya Meningkatkan Daya Tarik Wisata Muria - Firmandito, Rifqi Dwiyana; Listyorini, Tri; Supriyati, Endang (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2022)
Information and promotions are very important to introduce an area. The tourism potential for the Muria Mountains is an indication of natural wealth and products that deserve to be proud of. Village products found in Muria must be spread throughout the community and known by the wider community. However, due to the lack of information media dedicated to the Muria Mountains in Kudus Regency. Literature study, interviews, and observations were used to obtain data for this research. Waterfall approach is used in the system development process, codeigniter framework, and MySQL database are used. The black box testing approach is used in the system testing process. The purpose of this research is create a Dolan Muria web to introduce the tourist attraction of Muria and attract tourists to visit Muria. In this Dolan Muria application there is information about tourist destinations, typical Muria souvenirs, typical Muria cuisine, lodging, and transportation